Corporate Environmental Reporting: Do Firms Operating in Environmentally Sensitive Sectors Disclose Enough? - Abdulkadri Toyin Alabi; Olanrewaju Saheed Issa; Muhammed Kamaldeen Usman (Center for Science and Technology, IAIN Surakarta, 2024)
Corporate environmental disclosure has been increasing steadily as it is an essential factor for sustainable development. However, this factor seems to be insufficientl recognised within the Nigerian corporate world. The objective of this study is to assess the level of corporate sustainability disclosures in environmentally sensitive industries in Nigeria. This study is based on secondary data obtained from annual reports of firms listed on the Nigerian Exchange Group (NGX). Data used were collected from 45 sampled companies listed under 6 environmentally sensitive sectors for the 2021 financial year. Content analysis was applied to measure the level of environmental disclosures. The Environmental Disclosure Index (EDI) was prepared based on the Global Reporting Initiative (GRI) Standards. This research used independent sample t-test, analysis of variance, and the Kruskal-Wallis test as techniques of analysis. There were statistically significant differences in firms’ disclosure levels based on environmental certifications. The agriculture industry made the highest environmental disclosure, whereas the companies in the natural resources industry disclosed the least. It was found that companies revealed maximum information on their energy and environmental compliance initiatives, while there was inadequate information in other areas of environmental disclosure, such as neko77 supplier environmental assessment, effluents and wastes, and materials. The study provides implications for the strict adoption of a systematic reporting framework, especially for environmentally sensitive firms, while offering insights to guide policymakers, regulatory bodies, industry associations, and businesses in Nigeria to promote transparency and responsible environmental reporting.